The Role of Monetary and Fiscal Policies in Brazilian Hysteresis - Freitas, Raphael José Pereira; Vieira, Beatriz Estulano (Revista Economia Ensaios, 2025)
This paper uses a Vector Error Correction (VEC) model and Impulse Response Functions (IRFs) to identify macroeconomic shocks affecting real GDP and their implications for policymakers. The analysis reveals economic hysteresis in Brazil, with variables like the real exchange rate and net public sector debt exerting persistent effects on GDP. This underscores the importance of addressing structural factors. Fiscal adjustments emerge as vital for fostering confidence, supporting aggregate demand and highlighting the non-neutrality of fiscal policy. Structural limitations in the monetary transmission mechanism suggest that conventional monetary policy alone may be insufficient to achieve full employment, growth and financial stability.